Platycodon grandiflorum: from phytochemical diversity to polysaccharides' prominent bioactivities and edible-medicinal applications - Chen, Mengnan; Wei, Wenfeng; Wang, Zhuang; Huo, Jinhai; Wang, Weiming (Frontiers in Nutrition, 2026)
Platycodon grandiflorum (P. grandiflorum), a plant traditionally recognized for its dual application in medicine and food, is extensively utilized in East Asian traditional practices and culinary arts. This review consolidates recent findings on the phytochemical composition of P. grandiflorum, with an emphasis on the bioactivities, applications, and quality control of its key constituent—Platycodon grandiflorum polysaccharides (PGPs). The plant encompasses a variety of bioactive compounds, including saponins (with platycodin D as a marker), volatile oils, flavonoids, and PGPs, which are heteropolysaccharides predominantly composed of arabinose, galactose, and glucose. Notably, PGPs are distinguished by their non-toxicity, biocompatibility, and extensive therapeutic potential. Ultrasound-assisted extraction (UAE) methods have been shown to yield 22%−37% more PGPs than conventional techniques. These polysaccharides demonstrate significant immunomodulatory, antioxidant, metabolic regulatory, antitumor, and hepatorenal protective properties. While PGPs find utility in functional foods, pharmaceuticals, and cosmetics, challenges such as limited solubility persist. A robust quality control framework for PGPs is recommended. Future research endeavors should focus on strategic structural modifications, clinical assessments, and sustainable extraction methodologies to further its industrial applicability.